CHARACTERISTICS OF URINARY TRACT INFECTIONS IN PREGNANT WOMEN - I Gusti Ngurah Bagus Aditya Tirtayasa; Ni Wayan Widhidewi; Dewa Ayu Putri Sri Masyeni (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Urinary Tract Infection (UTI) is a common pregnancy complication and can seriously impact the health of the mother and fetus if not managed properly. This study aims to determine the characteristics of UTI in pregnant women. The study design used was a retrospective descriptive study with a cross-sectional approach, with a minimum sample size of 59 samples. Data collected came from secondary data in the form of medical records of pregnant women suffering from UTI at Klungkung Regional Hospital in 2021-2025. The collected data were analyzed descriptively using SPSS version 25. The results showed that UTI occurred most frequently in 2023, especially in pregnant women aged >35 years (66.1%) and in the second trimester of gestation (45.8%), with the majority being unemployed (57.6%). The most common clinical symptoms were suprapubic pain (27.4%), abdominal pain (17.9%), and fever (15.4%), with dominant urinalysis findings being cloudy urine, positive leukocyte esterase, positive urine erythrocytes, and positive bacteria (94.9%), and the most common pharmacological treatment was antibiotics (50%). The conclusion of this study indicates that UTIs in pregnant women are more common in the elderly reproductive age group and in the second trimester of pregnancy.